Analisis Kemampuan Komunikasi Matematis Siswa Kelas VIII-9 MTsN 1 Bukittinggi - Putra, Ilham Yani; Medika, Gema Hista; Isnaniah; Rahmat, Tasnim (Polinomial : Jurnal Pendidikan Matematika, 2025)
The purpose of this study was to evaluate students' mathematical communication skills in grades VIII-9 at MTsN 1 Bukittinggi. The approach used was descriptive quantitative, with implementation on May 6, 2024, and involving 32 students through purposive sampling techniques based on information from teachers regarding their low abilities. The data collection instrument was a descriptive test with 4 questions that reflected three indicators: connecting objects with mathematical concepts; expressing mathematical ideas, situations, and relationships; and expressing events or ideas in mathematical symbols. The results of the analysis showed that in general, students' mathematical communication skills were in the "sufficient" category, with an average score of 57.81. A total of 18 students (56.25%) were classified as "good", 8 students (25%) were in the "sufficient" category, and 6 students (18.75%) were in the "poor" category. In terms of indicators, students are best at connecting visual objects to mathematical ideas (average score of 81.25), followed by the ability to convey ideas through mathematical language or symbols (average score of 61.72), while the lowest results are in the indicator of explaining mathematical ideas (average score of 44.14).